Genome-wide insights into adaptive hybridisation across the Schistosoma haematobium group in West and Central Africa. - Toby Landeryou; Muriel Rabone; Fiona Allan; Rosie Maddren; David Rollinson; Bonnie L Webster; Louis-Albert; Roy M Anderson; Aidan M Emery (Public Library of Science (PLoS), 2022)
Schistosomiasis remains a public health concern across sub-Saharan Africa; current control programmes rely on accurate mapping and high mass drug administration (MDA) coverage to attempt disease elimination. Inter-species hybridisation can occur between certain species, changing epidemiological dynamics within endemic regions, which has the potential to confound control interventions. The impact of hybridisation on disease dynamics is well illustrated in areas of Cameroon where urogenital schistosomiasis, primarily due to Schistosoma haematobium and hybrid infections, now predominate over intestinal schistosomiasis caused by Schistosoma guineensis. Genetic markers have shown the ability to identify hybrids, however the underlying genomic architecture of divergence and introgression between these species has yet to be established. In this study, restriction site associated DNA sequencing (RADseq) was used on archived adult worms initially identified as; Schistosoma bovis (n = 4), S. haematobium (n = 9), S. guineensis (n = 3) and S. guineensis x S. haematobium hybrids (n = 4) from Mali, Senegal, Niger, São Tomé and Cameroon. Genome-wide evidence supports the existence of S. guineensis and S. haematobium hybrid populations across Cameroon. The hybridisation of S. guineensis x S. haematobium has not been demonstrated on the island of São Tomé, where all samples showed no introgression with S. haematobium. Additionally, all S. haematobium isolates from Nigeria, Mali and Cameroon indicated signatures of genomic introgression from S. bovis. Adaptive loci across the S. haematobium group showed that voltage-gated calcium ion channels (Cav) could play a key role in the ability to increase the survivability of species, particularly in host systems. Where admixture has occurred between S. guineensis and S. haematobium, the excess introgressive influx of tegumental (outer helminth body) and antigenic genes from S. haematobium has increased the adaptive response in hybrids, leading to increased hybrid population fitness and viability.